INTEGRATED LEARNING AS A MODERN APPROACH TO DEVELOPING COMMUNICATIVE COMPETENCE - Rashidova Gulshoda (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the role of integrative classroom activities in developing communicative competence in modern education. Integrated learning combines reading, writing, listening, and speaking skills into a unified educational process and enhances students’ critical thinking and collaboration abilities. The study analyzes different forms of integrative activities such as thematic instruction, inquiry-based learning, peer teaching, and technology integration. The findings indicate that integrative approaches improve students’ motivation and learning effectiveness by connecting academic knowledge with real-life situations.